2021
DOI: 10.3389/fphar.2021.753881
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rb1 Ameliorates Diabetic Arterial Stiffening via AMPK Pathway

Abstract: Background and Purpose: Macrovascular complication of diabetes mellitus, characterized by increased aortic stiffness, is a major cause leading to many adverse clinical outcomes. It has been reported that ginsenoside Rb1 (Rb1) can improve glucose tolerance, enhance insulin activity, and restore the impaired endothelial functions in animal models. The aim of this study was to explore whether Rb1 could alleviate the pathophysiological process of arterial stiffening in diabetes and its potential mechanisms.Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…The molecular mechanism of arterial stiffness caused by diabetes has also been widely investigated. Zhang et al found that diabetes can activate MMP2, MMP9, and TGFβ1/Smad2/3 pathways, leading to elevated blood pressure and arterial stiffness (46). Glucose fluctuations often occurs in patients with diabetes after meals.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism of arterial stiffness caused by diabetes has also been widely investigated. Zhang et al found that diabetes can activate MMP2, MMP9, and TGFβ1/Smad2/3 pathways, leading to elevated blood pressure and arterial stiffness (46). Glucose fluctuations often occurs in patients with diabetes after meals.…”
Section: Discussionmentioning
confidence: 99%
“…It may inhibit the increase in MDA content and the decrease in glutathione (GSH) levels in rat retinas and significantly increase the Nuclear Factor erythroid 2-Related Factor 2 (Nrf2) level and the expression of glutamate cysteine ligase catalytic subunit (GCLC) and glutamate cysteine ligase modifier subunit (GCLM) in rat retinal cell nuclei [57]. Ginsenoside Rb1 could also improve arteriosclerosis and prevent diabetic vasculopathy by reducing the inhibition of diabetes-induced Adenosine 5 ′ -monophosphate (AMP)-activated protein kinase (AMPK), regulating nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, alleviating oxidative stress, and inhibiting the TGFβ1/Smad2/3 pathway [58]. The mechanism of action of the fermentation extract in this experiment remains to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, Rb1 can lower blood glucose levels by modulating gut microbes, regulating lipid metabolism, and increasing insulin sensitivity. Moreover, it showed great efficacy in alleviating the occurrence of T2DM‐related complications, including diabetic cardiomyopathy (Qin et al, 2019; C. Zhang et al, 2022), diabetic atherosclerosis (Z. C. Wang, Niu, et al, 2022; X. Zhang et al, 2021), high glucose‐induced kidney damage or DN (J. Y. He et al, 2022), and high glucose‐induced cognitive impairment (R. Yang et al, 2020).…”
Section: Saponins In the Treatment Of T2dm And Its Complicationsmentioning
confidence: 99%